Implementasi Metode Persentase Penyelesaian untuk Pengakuan Pendapatan pada Perusahaan Jasa Konstruksi - Lunna Wuryandari; Nur Afiyati (BADAN PENERBIT STIEPARI PRESS, 2021)
This study examines the application of the percentage of completion method in revenue recognition in construction service companies, which is a sector with high complexity in revenue accounting. The percentage of completion method is used to record construction project revenue based on the extent to which the project has been completed, as an alternative to the complete completion method which may not accurately reflect the actual condition of the project. In this study, we analyze the effectiveness and challenges in applying this method with a focus on the accuracy of financial reporting and its impact on the company's income statement. The research method uses a case study approach by analyzing data from several construction companies that apply the percentage of completion method. The results show that this method can improve the accuracy of revenue recognition and provide a more realistic picture of project performance. However, challenges such as inaccurate cost estimates and changes in project scope remain issues that must be addressed. This research provides insights for construction companies and stakeholders in understanding the benefits and constraints of the percentage-of-completion method for more transparent and accurate revenue recognition.